The Planning of Bill of Quantity for the Construction of the Sibetan Village Market - I Gusti Agung Gede Nodya Dharmastika (Universitas Warmadewa, 2024)
The village of Sibetan in Bebandem District, Karangasem Regency, has promising potential in the agricultural sector, one of which is the snakeskin fruit. Most of the villagers in Sibetan own snakeskin fruit fields, which serve as their main source of livelihood. The distribution of this snakeskin fruit can be done by selling it at the market. However, the Sibetan village market does not yet have adequate facilities, so planning documents are needed for its development. The Bill of Quantity (BOQ) is one of the documents required to realize the construction. In this activity, the BOQ for the Sibetan village market will be prepared using the design already owned by the village authorities. The unit price method will be used to prepare the RAB for the Sibetan village market. The results of the activity indicate that the construction of the Sibetan village market requires a budget of IDR 701,950,397. The prepared BOQ will later be used to draft funding proposals, serve as a basis for decision-making, contract drafting, and cost control during the construction implementation.